2015
DOI: 10.1007/s11121-015-0556-9
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence and Substance Use as Longitudinal Predictors of Adolescents’ Risky Sexual Behavior

Abstract: Objective To examine dating violence perpetration and victimization (physical, psychological, and sexual) and lifetime substance use (alcohol, marijuana, and hard drugs) as longitudinal predictors of adolescents’ risky sexual behavior across one year, and to determine whether predictors varied across adolescents’ gender and ethnicity. Methods A sample of Caucasian, African American, and Hispanic male and female adolescents from 7 public high schools in Texas (N = 882) participated. Adolescents completed self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 43 publications
3
41
1
Order By: Relevance
“…In crude (i.e., unadjusted) models, each of the three studies with adolescent samples demonstrated a statistically significant association between marijuana use and PDV victimization either in sex-pooled (Yan et al, 2010; Shorey et al, 2015) or sex-stratified analyses (Eaton et al, 2007; Yan et al, 2010). Shorey et al (2015) did not include adjusted models, but the other two studies did.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In crude (i.e., unadjusted) models, each of the three studies with adolescent samples demonstrated a statistically significant association between marijuana use and PDV victimization either in sex-pooled (Yan et al, 2010; Shorey et al, 2015) or sex-stratified analyses (Eaton et al, 2007; Yan et al, 2010). Shorey et al (2015) did not include adjusted models, but the other two studies did.…”
Section: Resultsmentioning
confidence: 92%
“…The supplemental PsycInfo search yielded two additional articles (Shorey et al, 2014b; Foshee et al, 2010). In total, 13 articles were included in this review; two examined victimization (Eaton et al, 2007; Yan et al, 2010), eight examined perpetration (Foshee et al, 2010, McNaughton Reyes et al, 2014, Nabors, 2010, Rothman et al, 2010, Shorey et al, 2014a, Shorey et al, 2014b, Temple et al, 2011, Walton et al, 2009), and three examined both victimization and perpetration (Epstein-Ngo et al, 2013; Melander et al, 2010, Shorey et al, 2015). Relevant information about the studies (i.e., sample, design, measurement and prevalence of PDV and marijuana use, and measures of association) is summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Such additive effects of risky behaviors are in line with research showing risky behaviors undertaken during adolescence tend to co-occur with one another. For example, both cross-sectional (Neal & Fromme, 2007) and prospective research (Shorey et al, 2015) have demonstrated that risky sexual behavior is associated with other harmful risk-taking behaviors such as substance use. Risky sexual behavior has also been linked to later delinquency (Armour & Haynie, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of sexual TDV, which is more frequently perpetrated by males, the prevalence of TDV is similar for both genders (Shorey et al, 2008). In addition, victims of TDV, relative to non-victims, evidence a number of negative outcomes, including depressive and posttraumatic stress symptomatology (Exner-Cortens et al, 2013; Wolitzky-Taylor et al, 2008), alcohol and drug use (Parker, Debnam, Pas, & Bradshaw, 2016), sexually transmitted infections and risky sexual behavior (Silverman, Raj, Mucci, & Hathaway, 2001; Shorey et al, 2015), and suicidal ideation (Nahapetyan, Orpinas, Song, & Holland, 2014). Thus, it is imperative that effective primary prevention programs for TDV perpetration be implemented.…”
mentioning
confidence: 99%